UPRmt and coordinated UPRER in type 2 diabetes - Zhanfang Kang; Feng Chen; Wanhui Wu; Rui Liu; Tianda Chen; Fang Xu; Fang Xu (Frontiers in Cell and Developmental Biology, 2022)
The mitochondrial unfolded protein response (UPRmt) is a molecular mechanism that maintains mitochondrial proteostasis under stress and is closely related to various metabolic diseases, such as type 2 diabetes (T2D). Similarly, the unfolded protein response of the endoplasmic reticulum (UPRER) is responsible for maintaining proteomic stability in the endoplasmic reticulum (ER). Since the mitochondria and endoplasmic reticulum are the primary centers of energy metabolism and protein synthesis in cells, respectively, a synergistic mechanism must exist between UPRmt and UPRER to cooperatively resist stresses such as hyperglycemia in T2D. Increasing evidence suggests that the protein kinase RNA (PKR)-like endoplasmic reticulum kinase (PERK) signaling pathway is likely an important node for coordinating UPRmt and UPRER. The PERK pathway is activated in both UPRmt and UPRER, and its downstream molecules perform important functions. In this review, we discuss the mechanisms of UPRmt, UPRER and their crosstalk in T2D.